A reciprocal feedback loop between HIF-1α and HPIP controls phenotypic plasticity in breast cancer cells - Khumukcham, Saratchandra Singh; Penugurti, Vasudevarao; Soni, Anita; Uppala, Veena; Hari, Kishore; Jolly, Mohit Kumar; Dwivedi, Anju; Salam PK, Abdul; Padala, Chiranjeevi; Mukta, Srinivasulu; Bhopal, Triveni; Manavathi, Bramanandam (Cancer letters, 2022)
While phenotypic plasticity is a critical factor contributing to tumor heterogeneity, molecular mechanisms underlying this process are largely unknown. Here we report that breast cancer cells display phenotypic diversity in response to hypoxia or normoxia microenvironments by operating a reciprocal positive feedback regulation of HPIP and HIF-1α. We show that under hypoxia, HIF-1α induces HPIP expression that establishes cell survival, and also promotes cell migration/invasion, EMT and metastatic phenotypes in breast cancer cells. Mechanistic studies revealed that HPIP interacts with SRP14, a component of signal recognition particle, and stimulates MMP9 synthesis under hypoxic stress. Whereas, in normoxia, HPIP stabilizes HIF-1α, causing the Warburg effect to support cell growth. Concurrently, mathematical modelling corroborates this reciprocal feedback loop in enabling cell-state transitions in cancer cells. Clinical data indicate that elevated levels of HPIP and HIF-1α correlate with unfavorable prognosis and shorter survival rates in breast cancer subjects. Together, this data shows a reciprocal positive feedback loop between HPIP and HIF-1α that was unknown hitherto. It unveils how the tumor microenvironment influences phenotypic plasticity that has an impact on tumor growth and metastasis and, further signifies considering this pathway as a potential therapeutic target in breast cancer. •Phenotypic plasticity drives breast cancer celladaptation under hypoxia via HIF-1α-HPIP axis.•In hypoxia, HIF-1α drives HPIP and SRP14 transcription which regulate MMP9 translation promoting invasion and metastasis.•In normoxia, HPIP stabilizes HIF-1α via PI3K/AKT/GSK3β pathway promoting Warburg effect in breast cancer cells.•Mathematical modelling also supports HIF-1α-HPIP regulatory loop controlling phenotypic switching in breast cancer cells.